Effects of biochars on the bioaccessibility of phenanthrene/pyrene/zinc/lead and microbial community structure in a soil under aerobic and anaerobic conditions - Ni, Ni; Shi, Renyong; Liu, Zongtang; Bian, Yongrong; Wang, Fang; Song, Yang; Jiang, Xin (Journal of environmental sciences (China), 2018)
The immobilization of co-contaminants of organic and inorganic pollutants by biochar is an efficient remediation strategy. However, the effect of biochar amendments on the bioaccessibility of the co-contaminants in dry versus flooded soils has rarely been compared. In batch experiments, bamboo-derived biochar（BB） had a higher sorption capacity for phenanthrene（Phe）/pyrene（Pyr）/zinc（Zn） than corn straw-derived biochar（CB）, while CB had a higher sorption capacity for lead（Pb） than BB. After 150 days of incubation, the amendments of 2% CB, 0.5% BB and 2% BB effectively suppressed the dissipation and reduced the bioaccessibility of Phe/Pyr by 15.65%/18.02%, 17.07%/18.31%and 25.43%/27.11%, respectively, in the aerobic soils. This effectiveness was more significant than that in the anaerobic soils. The accessible Zn/Pb concentrations were also significantly lower in the aerobic soils than in the anaerobic soils, regardless of treatments.The Gram-negative bacterial biomass and the Shannon–Weaver index in the aerobic soil amended with 2% CB were the highest. The soil microbial community structure was jointly affected by changes in the bioaccessibility of the co-contaminants and the soil physiochemical properties caused by biochar amendments under the two conditions. Therefore, dry land farming may be more reliable than paddy soil cultivation at reducing the bioaccessibility of Phe/Pyr/Zn/Pb and enhancing the soil microbial diversity in the short term.